Evidence and Prosecution of Out-Of-Wedlock Pregnancies: A Legal Perspective of Syariah Criminal Offences in Malaysia - Bahori, Adibah; Mat Rashid, Azizah; Yahya, Mohamad Azhan; Saifuddin, Suhaizad; Mat Salleh, Mohd Kamel (UUM Press, 2023)
The issue of illegitimate pregnancies is worrying and births out of wedlock are rampant in Malaysia. These concerns are not exclusive to Malaysia however, as typically, developing countries encounter similar problems. Workable data or statistics on adultery are nearly impossible to obtain as the perpetrator would be unlikely to plead guilty, unless there are reliable witnesses willing to testify and help the prosecution. However, data on out of wedlock pregnancies and illegitimate births in Malaysia are certainly considered essential indicators of acts of fornication. Apart from from the incidences of rape, acts of voluntary sexual intercourse also contribute to both pregnancies and the birth of illegitimate children. Against this backdrop, the present paper aims to analyse the relevant syariah criminal laws related to premarital pregnancies. The areas of interest are issues on the allocation of funds, nature of punishment, extent of prosecution, and incriminating evidence required under the Syariah Criminal Offences (SCO) Enactments of states in Malaysia. This study has adopted a qualitative method by obtaining data through analyses of documents pertaining to the Syariah Criminal Offences (SCO) Enactments of Malaysian states, books, and academic journals. This study finds that not all states have provisions for extramarital affairs. In fact, prosecutions in Syariah Courts for out of wedlock pregnancies are very few compared to the number of illegitimate births. In addition, the existing provisions under the SCO are sufficient to handle cases of out of wedlock pregnancies and illegitimate births. In facing this reality, effective laws are obligatory, on top of the need to refine the existing provisions and develop the Islamic legal and judicial system in Malaysia.